An integrative review of patient safety in studies on the care and safety of patients with communication disabilities in hospital. Issue 4 (April 2016) - Hemsley, Bronwyn; Georgiou, Andrew; Hill, Sophie; Rollo, Megan; Steel, Joanne; Balandin, Susan
Highlights: We reviewed 27 studies on the care of patients with communication disabilities. Accounts of patient safety incidents were extracted from the studies for analysis. Further information is needed on factors contributing up to and following patient safety incidents. Family and paid carers may be a protective factor in relation to patient safety incidents. Hospital staff need to listen to patients and carers who raise concerns about care. Abstract: Objective: To review the research literature on the experiences of patients with communication disabilities in hospital according to the Generic Model of patient safety. Methods: In 2014 and 2015, we searched four scientific databases for studies with an aim or result relevant to safety of hospital patients with communication disabilities. The review included 27 studies. Results: A range of adverse event types were outlined in qualitative research. Little detail was provided about contributing or protective factors for safety incidents in hospital for these patients or the impact of the incidents on the patient or organisations involved. Conclusion: Further research addressing the safety of patients with communication disabilities is needed. Sufficient detail is required to identify the nature, timing, and detection of incidents; factors that contribute to or prevent adverse events; and detail the impact of the adverse events. Practice implications: In order to provide safe and effective care to people with communication disabilities in hospital, a priority for health and disability services must be the design and evaluation of ecologically appropriate and evidence-based interventions to improve patient care, communication, and reduce the risk of costly and harmful patient safety incidents.